Implementation of Science and Technology Concepts in Blind Stick STEM Project through the Engineering Design Process - Lukman Nulhakim; Reza Setiawan (SEAQIS Journal of Science Education, 2021)
STEM education plays an important role in developing the 21st-century skills of the students moreover it can also increase students' understanding of science and technology concepts and how to apply their knowledge to solve a real-life problem. The improvement of students' increased understanding of concepts is hypothetically linked to the engineering design process that happened in STEM learning. This study aims to identify how students apply their prior science-technology concept to develop a smart blind stick through the engineering design process (EDP). The descriptive case study method includes direct observations, interviews, and documentation analysis in 3 STEM lessons of 30 high school students were conducted. During three STEM lessons, students are improving their skills to apply their prior science concepts to solve the challenge, students also introduce to knowledge of coding in order to develop a smart blind stick project. This study shows an example of how the engineering design process facilitates the application of science-technology knowledge in solving given problems. To support the learning process the teacher uses scaffolding techniques and optimizes the engineering design process, especially at the research step.